AMOSTRAGEM DE CIGARRINHAS (HEMIPTERA, CICADELLIDAE) ATRAVÉS DE ARMADILHAS DE MOERICKE EM CAFEEIRO ARÁBICA - Lara, R.i.r.; Perioto, N.w.; Freitas, S. De [UNESP] (Instituto Biológico, 2022)
This study had for objective to evaluate the population fluctuations of the leafhoppers (Hemiptera, Cicadellidae) associated to Coffea arabica in Cravinhos, São Paulo, Brazil. The leafhoppers were sampled weekly by using 60 Moericke trap in the period of April/2005 to April/2006. Were collected 3.243 leafhoppers belonging to eight species: Bahita infuscata, Coelidiana diminuta, Dilobopterus costalimai, Docalidia bifurcata, Joruma (Joruma) sp., Labocurtidia sp., Oncometopia facialis and Scaphytopius irrorellus. The mostly frequency of the leafhoppers associated at coffee crop occurred in the rainy season; all the species of Cicadellidae collected were constants and the Moericke traps located at the median third of the plants were preferred for the capture of this group of insects. D. costalimai presented positive and significant correlations (p < 0.05) with the rainfall and maximum and minimum temperatures and O. fascialis was only with minimum temperature.

Este estudo teve por objetivo avaliar o padrão de variação populacional de cigarrinhas (Hemiptera, Cicadellidae) associadas ao cafeeiro, em Cravinhos, SP. As amostragens foram realizadas, semanalmente, no período de abril de 2005 a abril de 2006 através de 60 armadilhas de Moericke instaladas nos terços médio e inferior das plantas. Foram coletados 3.243 exemplares de cigarrinhas pertencentes a 8 espécies: Bahita infuscata, Coelidiana diminuta, Dilobopterus costalimai, Docalidia bifurcata, Joruma (Joruma) sp., Labocurtidia sp., Oncometopia facialis e Scaphytopius irrorellus. As maiores abundâncias destes cicadelídeos associados à cultura do cafeeiro ocorreram no período chuvoso; as espécies de cicadelídeos coletadas foram constantes e as armadilhas de Moericke instaladas no terço médio das plantas foram mais eficientes para a captura deste grupo de insetos. Verificou-se correlação positiva significativa entre os valores populacionais de D. costalimai com a pluviosidade e as temperaturas máxima e mínima e, para O. facialis, foi apenas com a temperatura mínima.
SAMPLING OF LEAFHOPPERS (HEMIPTERA, CICADELLIDAE) BY USING MOERICKE TRAP IN COFFEE CROP
Keywords: Coffea arabica; diversity; population fluctuation; vectors leafhoppers; Xylella fastidiosa; Cigarrinhas vetoras; Coffea arabica; diversidade; flutuação populacional; Xylella fastidiosa